IMPLEMENTASI INKUIRI TERBIMBING DENGAN MEDIA BAAMBOOZLE PADA MATERI ZAT ADITIF UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA - Tri Ambar Wati, Desi; Puspitarini, Sapti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low critical thinking skills of students and learning is still dominated by conventional learning. The purpose of this study is to describe the critical thinking skills of students before and after the implementation of guided inquiry with Baamboozle media on the topic of additives. The study used a one-group pretest-posttest design conducted in one of the State Junior High Schools in Surabaya City with 30 eighth-grade students as subjects. The data collection technique in this study used a test. The research instrument consisted of a test sheet to measure critical thinking skills. The data obtained were analyzed using N-Gain, normality test, paired t-test, and descriptive analysis based on the mode value. The results of the study showed an increase in critical thinking skills with an N-Gain value of 0.58 in the moderate category. Based on this explanation, students' critical thinking skills can be improved by implementing a guided inquiry model with Baamboozle media, especially on the topic of additives.